ANALISIS DETERMINAN NILAI EKSPOR PINANG DI PROVINSI JAMBI - Khoirudin, Rifki (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Indonesia is known as an agricultural country. This nickname is no doubt because the abundance of natural resources such as agriculture, plantations, and so on is an opportunity for export trade. In addition to oil and gas, Indonesia also exports non-oil and gas, one of which is areca nut. There are betel nut plantations covering an area of ​​152 thousand hectares, with this in 2017 Indonesia’s areca nut is in the 29th position from all over the world. Of the total land, 22 thousand hectares of which are in Jambi Province. Jambi Province has exported areca nut to several areas in East and South Asia to the Pacific Islands, which are used as chemical raw materials such as the pharmaceutical industry, cosmetic ingredients, preservatives to fabric dyes. This study aims to determine the factors that affect the export value of areca nut in Jambi Province. This type of quantitative research uses secondary data based on the time series time horizon for the period 2014 to 2022 (quarterly data) originating from the BPS official website, BI Report, and the Jambi Province Ministry of Agriculture. Processed using multiple linear regression model. Based on the results, it is concluded that the exchange rate of the US dollar against the rupiah has a positive and significant impact, the central bank interest rate has a negative and significant impact on the value of Jambi Province betel nut exports. While the consumer price index and economic growth in Jambi Province did not significantly affect the export value of betel nut in Jambi Province.